1998
DOI: 10.1063/1.869703
|View full text |Cite
|
Sign up to set email alerts
|

Large deformation of red blood cell ghosts in a simple shear flow

Abstract: Red blood cells are known to change shape in response to local flow conditions. Deformability affects red blood cell physiological function and the hydrodynamic properties of blood. The immersed boundary method is used to simulate three-dimensional membrane-fluid flow interactions for cells with the same internal and external fluid viscosities. The method has been validated for small deformations of an initially spherical capsule in simple shear flow for both neoHookean and the Evans-Skalak membrane models. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
323
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(347 citation statements)
references
References 36 publications
16
323
1
2
Order By: Relevance
“…Larger deformations from sphericity can be explored by numerical simulations. A body of work exists on capsule dynamics, mostly considering elastic membranes with no bending resistance 40,41,42 . To our knowledge there are only a couple of numerical studies that include bending resistance 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Larger deformations from sphericity can be explored by numerical simulations. A body of work exists on capsule dynamics, mostly considering elastic membranes with no bending resistance 40,41,42 . To our knowledge there are only a couple of numerical studies that include bending resistance 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…The cells are modeled as three-dimensional elastic capsules containing a Newtonian liquid, and the fluid flow is governed by the continuity and Stokes momentum balance equations (Eggleton and Popel, 1998;Jadhav, et al, 2005):…”
Section: Problem Statementmentioning
confidence: 99%
“…Deformation was found to increase with an increase in the capillary number. Large deformation of red blood cell ghosts was simulated by (Eggleton and Popel, 1998) using the Immersed Boundary Method (IBM) that reproduced the tank treading behavior observed experimentally in shear flow (Fischer, et al, 1978). (Lac and Barthes-Biesel, 2005) computed elastic capsule deformation in simple shear flow and hyperbolic flow using the Boundary Element method, and showed that steady shapes were obtained only within stable capillary number ranges.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the fluid and immersed boundary can be modeled by a well chosen discretized approximation to the Dirac delta function, which is called a discrete delta function. This approach has been applied successfully to problems of blood flow pattern in the heart [20][21][22][23][24], wave propagation in the cochlea [3,12], flow in collapsible tubes [27], aquatic animal locomotion [7][8][9], platelet aggregation during blood clotting [8,11], the flow of suspensions [10,30], flow and transport in a renal arteriole [1], and the cell and tissue deformation under shear flow [4,6,29].…”
Section: Introductionmentioning
confidence: 99%